A three-armed cognitive-motor exercise intervention to increase spatial orientation and life-space mobility in nursing home residents: study protocol of a randomized controlled trial in the PROfit project - Wollesen, Bettina; Fricke, Madeleine; Jansen, Carl-Philipp; Gordt-Oesterwind, Katharina; Schwenk, Michael; Muehlbauer, Thomas; Morawietz, Christina; Kruse, Adele; Gramann, Klaus (BMC geriatrics, 2020)
In nursing home residents, the combination of decreasing mobility and declining cognitive abilities, including spatial orientation, often leads to reduced physical activity (PA) and life-space (LS) mobility. As a consequence of sedentary behavior, there is a lack of social interaction and cognitive stimulation, resulting in low quality of life. It has not yet been examined whether cognitive-motor training including spatial cognitive tasks is suitable to improve spatial orientation and, as a consequence, to enlarge LS mobility, and increase well-being and general cognitive-motor functioning. Therefore, the overall goal of this multicentric randomized controlled trial (RCT) is to compare the effect of three different intervention approaches including functional exercise and orientation tasks on PA, LS and spatial orientation in nursing home residents.